2015
DOI: 10.1007/s40415-015-0149-7
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous application of trehalose alters growth, physiology and nutrient composition in radish (Raphanus sativus L.) plants under water-deficit conditions

Abstract: Radish (Raphanus sativus L.) is one of the most desirable vegetables grown in many parts of the world due to its short growth period and high nutritious value. To explore its cultivation in rain-fed areas, the present study was conducted to assess the role of foliar-applied trehalose (25 and 50 mM) in two radish cultivars, Manu and 40-days, grown under non-stress (100 % FC) and water stress (60 % FC) conditions. Under drought stress conditions, shoot fresh and dry weights, shoot and root lengths, photosyntheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 38 publications
3
10
0
2
Order By: Relevance
“…However, it is well reported that plants modulate their physio-biochemical processes and anatomical features according to the internal or external climate so as to survive under such harsh conditions (Shafiq et al, 2015;Akram et al, 2016). In the present study, plant growth measured as shoot and root dry weights of both oat cultivars decreased under water deficit conditions, which is in agreement with some earlier findings which also reported a water stress-induced decline in growth of various crops such as wheat (Jatoi et al, 2011;Raza et al, 2012), mungbean (Sadiq et al, 2017), sugar beet (Bloch et al, 2006), grasses (Akram et al, 2007), maize (Zhang et al, 2012) and radish (Akram et al, 2015). They found that water stress-reduced plant growth is linked to the interior status of the plant with respect to specifically photosynthesis, nutrients, hormones, antioxidants, primary and secondary metabolites, fluorescence, quantum use efficiency, respiration, and photosynthetic pigments, etc.…”
Section: Discussionsupporting
confidence: 92%
“…However, it is well reported that plants modulate their physio-biochemical processes and anatomical features according to the internal or external climate so as to survive under such harsh conditions (Shafiq et al, 2015;Akram et al, 2016). In the present study, plant growth measured as shoot and root dry weights of both oat cultivars decreased under water deficit conditions, which is in agreement with some earlier findings which also reported a water stress-induced decline in growth of various crops such as wheat (Jatoi et al, 2011;Raza et al, 2012), mungbean (Sadiq et al, 2017), sugar beet (Bloch et al, 2006), grasses (Akram et al, 2007), maize (Zhang et al, 2012) and radish (Akram et al, 2015). They found that water stress-reduced plant growth is linked to the interior status of the plant with respect to specifically photosynthesis, nutrients, hormones, antioxidants, primary and secondary metabolites, fluorescence, quantum use efficiency, respiration, and photosynthetic pigments, etc.…”
Section: Discussionsupporting
confidence: 92%
“…However, exogenous trehalose improved the growth of tomato and increased the plant height, fresh mass, and the relative water content of tomato leaves, especially under treatment with 2 mmol/L trehalose, which was consistent with the results in Ref. [27]. Salt stress affects photosynthesis in plants.…”
Section: Screening For Optimal Trehalose Concentrationsupporting
confidence: 90%
“…The fortification of trehalose significantly decreased the RMP in both sunflower cultivars. Similarly, Akram et al (2015) reported that application of trehalose decreased RMP in dehydrated radish plants. So, it can be suggested that trehalose plays a role in stabilizing membrane integrity, thus acting as an important membrane stabilizer.…”
Section: Discussionmentioning
confidence: 86%